2017
DOI: 10.1210/jc.2017-02019
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Exercise Decreases IP6K1 Muscle Content and Improves Insulin Sensitivity (SI2*) in Glucose-Intolerant Individuals

Abstract: The in vivo and in vitro approaches used in the current study suggest that a decrease in muscle IP6K1 may be linked to whole body increases in SI2*. In addition, high-intensity exercise reduces hepatic glucose production in insulin-resistant individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 72 publications
3
31
0
Order By: Relevance
“…This is the first study to characterize IGF-1/IP6K1/Akt signalling in skeletal muscle and postprandial circulating proteome after lean meat ingestion, a common component of a western dietary pattern, in sedentary young adults of various BMIs and fat masses. The novel finding here is that muscle IP6K1 protein content is elevated in individuals with obesity after the ingestion of lean meat when compared to lean adults, suggesting that IP6K1 may be implicated in the reduction of nutrient uptake in skeletal muscle in the post-absorptive state in obese individuals [13]. Our data also showed that IGFR signalling in skeletal muscle is elevated in the obese phenotype which is present in the face of reduced plasma IGF-1 in the same population compared to lean controls.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This is the first study to characterize IGF-1/IP6K1/Akt signalling in skeletal muscle and postprandial circulating proteome after lean meat ingestion, a common component of a western dietary pattern, in sedentary young adults of various BMIs and fat masses. The novel finding here is that muscle IP6K1 protein content is elevated in individuals with obesity after the ingestion of lean meat when compared to lean adults, suggesting that IP6K1 may be implicated in the reduction of nutrient uptake in skeletal muscle in the post-absorptive state in obese individuals [13]. Our data also showed that IGFR signalling in skeletal muscle is elevated in the obese phenotype which is present in the face of reduced plasma IGF-1 in the same population compared to lean controls.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, evidence in rodent and in vitro models suggests that inositol hexakisphosphate kinase 1 (IP6K1) reduces insulin sensitivity and inhibits glucose uptake [11,12]. This is supported by recent work from our laboratory which showed decreased IP6K1 skeletal muscle content and improved insulin sensitivity in response to muscle contraction in pre-diabetic humans [13]. IP6K1 is known to synthesize IP6 to IP7 which binds to the pleskstrin homology (PH) domain of Akt, preventing translocation to the cell membrane [12].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this anomaly was not found in 405 unrelated patients, indicating that the disruption is either family-specific or a chance association. The expression of Ip6k1 correlates inversely with insulin sensitivity [229], whereas both Ip6k1 and Ip6k2 expression directly correlate with hepatocellular carcinoma (HCC) [230]. Ip6k3 is upregulated in NAFLD patients [231].…”
Section: Ip6ks In Human Metabolic Diseasesmentioning
confidence: 99%
“…Presumably, the abundance of IP6 keeps the IP6/IPP ratio high/optimum, which is required for the metabolic health of cells or tissues. However, in metabolic aberrations such as insulin resistance [229], HCC [230], NAFLD [231] and aging [22,44], Ip6k expression or IP7 level increases, which is expected to reduce the IP6/5-IP7 ratio. In such conditions, restoring this ratio to its normal level may ameliorate these diseases.…”
Section: Can the Ratio Of Ip6/ipp Be Targeted In Metabolic Diseases?mentioning
confidence: 99%